Hereditary factors and syndromes of genetic predisposition related to sarcomas of soft parts - Carlos Juan Puig González; Juan Carlos Puig Chong; Lianet Castro Bolano (Centro Provincial de Información de Ciencias Médicas, 2022)
The sarcomas of soft parts are malignancies that originate in the connective tissue, starting from the embryonic mesenchyme. Taking into account the existence of new and constant changes in the nature of these tumors, a review of the most recent publications was carried out to deepen in the genetic disorders, the predisposing syndromes and its relationship with sarcomas. It was concluded that the records that describe the identification of these syndromes are still very few as main link in the development of sarcomas.